The contribution of Lembaga Tabung Haji to Muslim society: source of study from Tabung Haji Temerloh / Muhammad Muhsein Ahmad Fadzil - Ahmad Fadzil, Muhammad Muhsein (2018)
Today, Lembaga Tabung Haji is not only responsible for safeguarding the welfare of before from the aspects of health, transportation, and accommodation but also strive to protect before from any form of deception and exploitation of various parties. Various difficulties experienced by the Malays to realize ambitions perform Hajj also change gradually with the implementation of a more systematic management of Hajj and orderly manner. Disclosures elsewhere and guidance given by the Lembaga Tabung Haji to before, particularly the Malays limit resulted in many elements of the heretics and superstitious related to successful pilgrimage left, though could not be deleted completely and to be given this course. The research objectives are wanted to provide detailed disclosure and explanation on the donation of the Hajj fund to the general public. And then, aims to show to the community that the hajj board performs its duties in contributing to the development of the Islamic Ummah in Malaysia. And lastly, the objective is to explore the contribution of the Tabung Haji into Islam citizens in scope of Malaysia board. In order to achieve all these objectives, the authors use the primary method by using the interview and also more historical method. The sources of research carry out from Tabung Haji Temerloh, Pahang.